(untitled) (Raparin Journal of Humanities (RJH), 2020)
The international organization is the criminal clause, an international organization specialized in the fight against crime in general and the organized crime , the term in particular, and this is due to the seriousness of this crime in various fields, and states can no longer can front it individually, given technological development, and with limited police competencies the interior the international community sought to find a mechanism capable of police cooperation among countries to confront organized crime . As this organization specializes in extraditing criminals and un covering unknown searches through coordination of security services between member states and plays a prominent role in the area of fighting transnational organized crime, the organization also works to prevent international crime through field and technical support to the police in the world working to confront growing international criminal challenges and I suggest spurious solutions to tackle these crimes and simplify the procedures for extraditing them to justice so that they can be punished without escaping them.